STUDENTS’ PERCEPTION ON THE USE OF MEDIA OF ADVERTISEMENTS IN TEACHING SOCIOLINGUISTICS - Vina Fathira (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2019)
The researcher wanted to evaluate the students’ opinion of using media of advertisements in order to get the deep description of the understanding of linguistic theory. Using media of advertisement is one of the techniques in increasing students’ understanding of linguistic matters, especially in teaching sociolinguistics, especially in politeness and gender concept. In digital era, using media of advertisement is familiar media seen by the students that is using gadget actively. The research aims at students’ perception of the use of media of advertisements in teaching sociolinguistics. The descriptive research was employed to this research. A group of students in a classroom using this media of advertisements is the population and the sample of this research. There were 10 students of the third year of STIBA Persada Bunda Pekanbaru through media of advertisement during 2017/2018 academic year. In collecting data, the students were asked to watch two videos from media of advertisements relating to politeness and gender. Then, in analysing data, the researcher used six questions relating to politeness and gender to the students by semi structured interview. The result indicated that most of the students motivated in obtaining information and enjoyed during the learning process and media of advertisement also increased their curiosity in understanding politeness and gender concepts of teaching sociolinguistics.